Effect of Annealing on the Optical Properties and the Refractive Index Dispersion of CdS Nanometer Films - V. Kusnezh; R. Petrus’; H. Il’chuk; O. Tuziak (Журнал нано- та електронної фізики)
The paper describes the optical properties of CdS ultrathin (~ 50 nm) films, fabricated by the chemical surface deposition on transparent glass substrates. The influence of the atmosphere (Ar2, CdCl2 and air) thermal annealing on the spectral dependence of the CdS films reflection coefficient R(λ) and absorption α(λ) was investigated. The extinction coefficient k(λ), refractive index n(λ), real ε1(λ) and imaginary ε2(λ) parts of the optical dielectric constant of the films annealed in different atmospheres were calculated using the experimental characteristics. The coefficients of Sellmeier equation to describe the n(λ) dependence in the visible and near infrared spectrum were determined.